Effect of Pruning on Cassava Stem, Foliage and Tuber Yield - S, Sunith; Ravindran, C S; George, James; Sreekumar, J (JOURNAL OF ROOT CROPS, 2016)
Field experiments were conducted for three years (2009-2012) to study the effect of pruning in cassava using three varieties (Sree Jaya, Sree Vijaya, and CE-347), three methods of pruning (pruning of 1/3rd top portion at 3rd month, pruning at 3rd and 6th months and no pruning and two nitrogen doses (100 and 125 kg ha-1) at ICAR-CTCRI, Thiruvananthapuram, Kerala. The treatments were assessed based on the total tuber yield, foliage yield and stem yield obtained. Pooled analysis of the three years data indicated significant difference with respect to the effect of pruning only and not for varieties or nitrogen levels. Control treatment without pruning recorded maximum tuber yield, however, it was on par with single pruning at 3rd month. Two prunings at 3rd and 6th months reduced the tuber yield significantly. Single pruning at 3rd month resulted in maximum foliage yield closely followed by pruning twice at 3rd and 6th month respectively. Leaf yield was less under no pruning. Stem yield was maximum with no pruning, but was on par with single pruning at 3rd month. Pruning twice significantly reduced the stem yield. So, wherever, foliage can be effectively used, single pruning can be practised without adversely affecting the tuber and stem yield of cassava.